Clinical Study on Risk Factors and Fetomaternal Outcome of Severe Preeclampsia in Bangabandhu Sheikh Mujib Medical University (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Preeclampsia (PE) especially severe or early PE, is a leading cause of morbidity and mortality among the mothers and infants.To determine the maternal risk factors and fetomaternal outcome of severe preeclampsia.Methods: It was a case control study, done in a tertiary care hospital among 100 patients with severe preeclampsia and normal pregnant women admitted. Sampling technique were consecutive sampling methods. Singleton pregnancy between 28 to 40 weeks of gestation with severe preeclampsia were selected as study patients. Written informed consent was obtained. A questionnaire was completed for each patient including patient's age, gestational age, parity, History of hypertension in family, weight and Body Mass Index (BMI). Maternal complications before or after delivery, and perinatal outcome were also be recorded in the data sheet. Data was analyzed by SPSS-20.Results: Among the 50 cases and 50 controls regarding different risk factors age >34 years, BMI, history of precelampsia, were found significant (p